Investigation of Antifungal Effect of Chlorella Protothecoides Microalgae Oil Against Botrytis cinerea and Aspergillus niger fungi - Ozcimen, Didem (UNIV NAMIK KEMAL, 2018)
Microalgae are natural rich sources of biologically active compounds such as antibiotics, antivirals, antitumorals and antioxidants. Furthermore, these microorganisms have the ability to promote health and reduce the risk of the development of degenerative diseases. In order to develop new pharmaceuticals and provide chemical and pharmacological innovations and diversity, the investigation of these biologically active compounds is very important. In this context, it is thought that microalgae oils obtained from various microalgae species have in vitro antimicrobial and/or antifungal activity against various microorganisms and can be used as fungistatic. In this this study, antifungal activities of Chlorella protothecoides microalgae oil dissolved in 50 and 100 mg/mL of dimethyl sulfoxide (DMSO), ethanol and methanol solvents against pathogenic fungi: Botrytis cinerea and Aspergillus niger was investigated by agar disc diffusion assay method. As a result of this study, it was seen that almost all of the extracts of microalgae have antifungal activity against Botrytis cinerea and Aspergillus niger pathogens. These results are an important indication of the presence of antifungal compounds in algae and algal species should be specifically investigated for the pharmaceutical industry.
Keywords: Saprophytic fungus; Antifungal activity; Microalgae; Chlorella protothecoides; POSTHARVEST DECAY; Agriculture